2017
DOI: 10.21272/jnep.9(6).06028
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Optical Absorption Properties of Copper Oxide Nanoparticles for Applications in Transparent Surface Coatings and Solar Cells

Abstract: A simple wet chemical method has been successfully deployed to synthesize CuO nanoparticles (NPs) by using copper chloride and lithium hydroxide as the precursors. X-ray diffraction study revealed that the synthesized CuO is highly crystalline and pure. The synthesized CuO NPs has very high transparency in the visible region of wavelength. The band gap of the CuO NPs was found to be 1.54 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Debanatth et al, 58 reported the bandgap energy of ZnO at low temperature (3.63 eV) and Evstropiev et al 59 measured ZnO samples with bandgap energy values around 3.93-4.13 eV. According to Samanta et al 60 and Miri et al, 61 the bandgap energy enhancement occurs due to the quantum confinement of carriers by the small dimensions of the nanocrystals. The Urbach's tail energy is usually estimated to evaluate crystallinity and disorder on materials.…”
Section: Resultsmentioning
confidence: 99%
“…Debanatth et al, 58 reported the bandgap energy of ZnO at low temperature (3.63 eV) and Evstropiev et al 59 measured ZnO samples with bandgap energy values around 3.93-4.13 eV. According to Samanta et al 60 and Miri et al, 61 the bandgap energy enhancement occurs due to the quantum confinement of carriers by the small dimensions of the nanocrystals. The Urbach's tail energy is usually estimated to evaluate crystallinity and disorder on materials.…”
Section: Resultsmentioning
confidence: 99%
“…Among various metal oxides, Zinc oxide (ZnO) which is one of the most important materials in the synthesis of solar cell applications has good optical properties which can observe in the fewer defects and less disorder. The semiconductor compounds as a ZnO has a n-type good electrical conductivity with a direct energy wide band gap of 3.37 eV at room temperature, a large exciton binding energy ( 60 meV) [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%